Effect of Right Ventricular Function and Venous Congestion on Cardio-Renal Interactions during the Treatment of Decompensated Heart Failure - Testani, Jeffrey M. (2010)
Recent reports have demonstrated the adverse effects of venous congestion on renal function and challenged the assumption that worsening renal function (RF) is driven by diminished cardiac output (CO). We hypothesized that diuresis in patients with right ventricular (RV) dysfunction, despite diminished CO, would lead to a reduction in venous congestion and resultant improvement in renal function. We reviewed consecutive admissions with a discharge diagnosis of heart failure (HF). RV function was assessed by multiple echocardiographic methods and those with ≥2 measures of RV dysfunction were considered to have significant RV dysfunction. Worsening RF was defined as an increase in creatinine of ≥0.3 mg/dL and improved RF as improvement in glomerular filtration rate ≥25%. A total of 141 admissions met eligibility criteria, 34% developed worsening RF. Venous congestion was more common in those with RV dysfunction (OR=3.3, p=0.009). All measures of RV dysfunction excluding RV dilation correlated with CO (p<0.05). Significant RV dysfunction predicted a lower incidence of worsening RF (OR=0.21, p<0.001) and higher incidence of improved RF (OR=6.4, p<0.001). CO emerged as a significant predictor of change in glomerular filtration rate during hospitalization in those without significant RV dysfunction (r=0.38, p<0.001). In conclusion, RV dysfunction is a strong predictor of improved renal outcomes in patients with acute decompensated HF, an effect likely mediated by relief of venous congestion.